Analysis of a three phase capacitor voltage balanced hybrid multi-level inverter with a three phase RL-load - Crescent O, Omeje; Damian B, Nnadi; Charles I., Odeh; Candidus U., Eya; Stephen E, Oti (International Journal of Engineering and Technology, 2020)
This paper outlined the basic concepts of two selected types of hybrid multi-level inverters that were capacitor voltage-source dependent. A natural capacitor voltage balancing involving hysteresis with redundant switching states was analyzed in this paper. Simulations using MATLAB 7.14 were carried out for an unbalanced and a well-balanced capacitor voltage supply under 0V, 100V and 200V pre-charged capacitor voltage conditions. A comparative analysis of the two types of hybrid multi-level inverters (Type A and Type B) with pertinent to %THD values of [35.77% and 23.79%] for Type A and [92.10% and 84.94%] for type B during fault occurrence were evaluated in this work. These harmonic values can lead to thermal run away and total malfunction of the semi-conductor switches. An experimental vali-dation of Type A hybrid multi-level inverter with a three level flying capacitor input stage and H-bridge output stage using a three phase RL-Load of 15â„¦ and 45mH was accomplished in the laboratory with results compared with the simulations for experimental verification.Â Â